Large area co‐plated bifacial n‐PERT cells with polysilicon passivating contacts on both sides. (28th February 2022) - Singh, Sukhvinder; Choulat, Patrick; Govaerts, Jonathan; van der Heide, Arvid; Depauw, Valérie; Duerinckx, Filip; Naber, Ronald; Lenes, Martijn; Renes, Marten; Tous, Loic; Poortmans, Jef
Abstract: In this work, we show the integration of polysilicon‐based passivating contacts in plated bifacial n‐type PERT (passivated emitter and rear totally diffused) solar cells. We show the viability of n‐PERT cells using two‐side passivating contacts with two‐side plated nickel/silver metallization. Compared with commercially available "TOPCon" cells with rear side passivated contacts only, n‐PERT cells with both side passivated contacts should enable the exploitation of the full potential of passivated contacts. We show that both n‐poly and p‐poly were applied and co‐plated successfully on both sides of n‐PERT solar cells. Considering the potential parasitic absorption losses on the front side of the device originating from p‐poly, we applied selective p‐poly by patterning. We compared two patterning methods for front side polysilicon: the masking and etch approach using inkjet printing and a simple and cost‐effective patterning method using UV laser oxidation. A best efficiency of 22.7% has been achieved with these cells so far on large area (244.3 cm 2 ) n‐type Cz, with a potential efficiency above 24%. Some of these co‐plated bifacial cells have been processed into one‐cell laminates using smart wire interconnection (SWCT) technology. These have passed thermal cycling (TC) tests as defined in IEC61215. Abstract : n‐Poly and p‐poly were applied and co‐plated successfully on both sides of n‐PERT solar cells. To limit the parasitic absorption losses on the front side of the device originating from p‐poly, we applied selective p‐poly by patterning. A best efficiency of 22.7% has been achieved with these cells so far on large‐area (244.3 cm 2 ) n‐type Cz wafers.